FDA in the twenty-first century : the challenges of regulating drugs and new technologies - Lynch, Holly Fernandez; Cohen, I. Glenn (New York : Columbia University Press, 2016)
In its decades-long effort to assure the safety, efficacy and security of medicines and other products, the Food and Drug Administration has struggled with issues of funding, proper associations with industry and the balance between consumer choice and consumer protection. Today, these challenges are compounded by the pressures of globalization, the introduction of novel technologies and fast-evolving threats to public health. With essays by leading scholars and government and private industry experts, this book addresses perennial and new problems and the improvements the agency can make to better serve the public good.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 18, 2016).
Keywords: United States. -- Food and Drug Administration; Drugs -- Law and legislation -- United States; Industry; Social services & welfare, criminology; Business & Management; Employee-ownership & co-operatives.; Licensing, gaming & club law